Ultrastructure of Chondrocytes in Osteoarthritic Femoral Articular Cartilage - Goya, Nj; Gupta, M; Joshi, K (Kathmandu University Medical Journal, 2015)
Background Osteoarthritis (OA) is a common problem in elderly, but it is not an inevitable feature of ageing. About 80-90% of individuals of both sexes have radiographic evidence of OA by the time they reach an age of 65. But not all of them have the symptoms like pain and decreased joint motion. Objective The objective of the present study was conducted to find out whether the osteoarthritic changes in human articular cartilage are similar to the ageing process or not. Methods Femoral articular cartilage specimens obtained from 13 osteoarthritic patients (52-80years) undergoing total knee replacement and 9 cadavers of same age group (50-80years) (control) were processed and studied under electron microscope. The ultrastructure of the cartilage from the two groups was compared with each other. Results Under the electron microscope, articular cartilage from control group had chondrocytes having a secretary cell characteristic with prominent nucleus and well developed organelles. In osteoarthritic cartilage, degenerating or necrotic chondrocytes were found. Nuclei of these chondrocytes appeared lobulated or indented. Chondrocytes below the fibrillated surface had dilated and irregular endoplasmic reticulum. Electron dense lipid deposits in the extracelluar matrix as well as intracytoplasmic glycogen deposits were much increased in osteoarthritic cartilage as compared to the control group. Amount of perinuclear intracytoplasmic fine filaments was also increased in the chondrocytes of osteoarthritic cartilage. Conclusion Ultrastructural findings of the osteoarthritic articular cartilage were much different from the ageing non-osteoarthritic cartilage. Hence, OA should be considered a specific process and not simply an inevitable feature of ageing. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12507 Kathmandu Univ Med J 2013; 43(3):221-225